THE COMINFORM EMIGRATION IN BULGARIA - Milan Milenković (Istorija 20. Veka)
The main aim of this paper is to analyze the organization and activities of the Yugoslav political emigration in Bulgaria from 1948. to 1955. As a Soviet-satellite, Bulgaria was one of the countries chosen by the political dissidents (after the Yugoslav split with Cominform) not only for the purpose of political asylum, but also for the continuation of their struggle against Yugoslav government. Research is mostly based on unpublished sources from the State Security Service (UDB) that are kept in the State Archives of Serbia, and also on relevant literature.